Synergistic Finance-Economic Integration Effects in the Eaeu as the Main Factor in the Effectiveness of the Functioning of the Whole Union - O.V. Korol, O.V. (Экономика и банки, 2018)
В статье проанализированы основные макроэкономические индикаторы, характеризующие эффективность функционирования Евразийского экономического союза. Рассмотрены перспективы дальнейшего развития ЕАЭС на основе синергетического и мультипликативного эффектов интеграции. Ключевые слова: Евразийский экономический союз, международная экономическая интеграция, разделение труда, взаимные инвестиции. The article describes main macroeconomic indicators which characterize the effectiveness of the functioning of the Eurasian Economic Union. The prospects for the further development of the EAEU based on the synergistic and multiplicative integration effects are considered.Keywords: Eurasian Economic Union, international economic integration, division of labor, mutual investments.